Technological Parameters and Evaluation of Antioxidant Enzymes from Sugarcane (Saccharum spp.) when Applied Chemical Ripeners - Moreira, B. R. A. [UNESP]; Viana, R. S. [UNESP]; Manarelli, F. [UNESP]; Viana, C. R. A. [UNESP]; Nakamune, A. C. M. S. [UNESP] (Brazilian Chemical Soc, 2018)
The aim of this study was to evaluate juice technological traits and antioxidant enzymes specific activities from sugarcane cultivars following chemical ripeners spraying. The field experiment had a randomized block design (with six replicates) in factorial arrangment (9x2): active ingredients (control 0.00 L ha(-1), ethephon 0.67 L ha(-1), glyphosate 0.35 L ha(-1), MTD 1.00 L ha(-1), trinexapacethyl 0.80 L ha(-1), sulfumeturon-methyl 0.02 kg ha(-1), ethephon 0.34 L ha(-1) plus glyphosate 0.15 L ha(-1), MTD 1.00 L ha(-1) plus glyphosate 0.15 L ha(-1), and sulfumeturon-methyl 0,02 kg ha(-1) plus glyphosate 0.15 L ha(-1)), and sugarcane cultivars (RB86-5156 and RB86-5453), respectively. Subsequent to crop harvest (carried out 60-days after chemical ripeners spraying) stalks and leaf samples were assessed to degrees Brix, Pol, purity, theoretical sugars recoverable (TSR), fibers, superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), and peroxidase (POD) specific activities. There was null hypothesis rejection at interactive level between causes of variation for CAT and POD; while SOD, PAX, and all juice traits were affected only at simple effects level. It was concluded that chemical ripeners management enhanced juice quality and antioxidant enzymatic system reactivity of sugarcane crop.
Keywords: Ethephon; glyphosate; ROS; phytorregulators